UZBEKISTAN'S COOPERATION WITH KAZAKHSTAN IN THE FIELD OF EDUCATION HAS REACHED A NEW LEVEL - Akhmadova Nafisa Akhmad qizi (Web of Journals Publishing, 2025)
Uzbekistan's relations with Kazakhstan, mutual exchanges, historical and cultural dialogues, mutual agreements and treaties were covered and analyzed based on sources. Uzbekistan's mutual cooperation with Kazakhstan in the social, cultural, scientific, and educational spheres was touched upon. On the basis of mutual agreements, achievements were achieved in the social, cultural, scientific, and educational spheres.
Keywords: Diplomatic relations, international cooperation, Central Asia, Kazakhstan, Tajikistan, diplomacy, embassy, politics, science and education, scientific and technical, healthcare, tourism, culture.